Contentious Dynamics Within the Social Turbulence of Environmental (In)justice Surrounding Wind Energy Farms in Oaxaca, Mexico - Ramirez, Jacobo (Journal of business ethics)
Businesses and governments in postcolonial countries frame investments in wind energy as efforts to address climate change and sustainable development. However, when wind energy projects encroach on indigenous peoples’ lives and land, there is often a lack of recognition and participation of these peoples and an unequal distribution of cost and benefits of such projects toward them, which leads to opposition against wind energy projects and often triggers conflicts for justice. Worryingly, such conditions have repeatedly resulted in the assassination of human rights defenders, which further inflames the conflict. Herein, I discuss these concepts based on a longitudinal study centered on a wind energy project in Oaxaca, Mexico, with the aim of exploring and understanding the conditions under which wind energy investments fail to respect current laws and norms, as well as the consequences of such negligence. My in-depth analysis of the actions of the government, businesses, and indigenous peoples revealed a phenomenon that is less discussed in environmental (in)justice research: the gradual and continuous transformation of indigenous peoples’ norms and behaviors away from their traditional economic and cultural livelihoods. This phenomenon helps to extend the conceptual understanding of environmental (in)justice with regard to social turbulence, which is defined as the unpredictable behavior of political and social systems in contexts in which existing laws, regulations, and norms regarding environmental justice are not observed. The concept of social turbulence of environmental (in)justice helps to explain how indigenous peoples sacrifice their territories, norms, and traditions to a technical solution to climate change and sustainable development.